Correction: The examination of graphene oxide for rechargeable lithium storage as a novel cathode material. Issue 46 (18th November 2021) - Wang, Da-Wei; Sun, Chenghua; Zhou, Guangmin; Li, Feng; Wen, Lei; Donose, Bogdan C.; Lu, Gao Qing (Max); Cheng, Hui-Ming; Gentle, Ian R.
Abstract : Correction for 'The examination of graphene oxide for rechargeable lithium storage as a novel cathode material' by Da-Wei Wang et al., J. Mater. Chem. A, 2013, 1, 3607–3612, DOI: ; 10.1039/C3TA01658G .